TAHLIL KIFAYATI TA’LIMI Al-LUGHATI AL- ARABIYATI FI AL-QARNI Al-HADI WA Al-‘ISYRIN - Ashari, Moh. Yahya; Mahfudhoh, Rifatul (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
The requirements for the progress of education refer to the development of cognitive skill, motor skill, and emotional skill. The twenty-first century is indicated by the advances of information, technology and digital components that affect aspects of human life, as well as the education body applied with regard to how to achieve competencies in this century. The purpose of this study is to reveal the competencies in the twenty-first century and to reveal the appropriate models of Arabic language teaching with the competencies in the twenty-first century. The research used the qualitative approach with the application of the library study method. As for the method of data analysis, it used the steps of the Mills and Huberman’s method of data reduction, presentation and conclusion. It shows that: (1) education competencies in the twenty-first century are known by the term “the 4Cs” covering critical thinking, communication, sharing, innovation and creativity. (2) The models in teaching the Arabic language are the ones that encourage students’ active participation and independence in learning. The most important models are the reading and writing learning, the cooperative education, and the scientific education models. The main final outcome of this research is to achieve the four competencies of education in the twenty-first century, and the application of active learning models in the educational process.